Detection of O25b-ST131 clone, CTX-M-1 and CTX-M-15 genes via real-time PCR in Escherichia coli strains in patients with UTIs obtained from a university hospital in Istanbul - Mehmet Demirci; Özge Ünlü; Ayşe İstanbullu Tosun (Elsevier, 2019)
Background: Escherichia coli sequence type 131 is an important multidrug resistant clone responsible from more than half of ESBL-producing E.coli isolates. Aim of this study was to investigate the presence of O25b-ST131 clone, CTX-M-15 and CTX-M-1 genes in the E. coli strains isolated from both hospital and community acquired UTIs by real-time PCR and to reveal molecular epidemiological data. Methods: Non-duplicate E. coli (n = 101) strains isolated from UTI patients were included. Bacterial identifications were performed with VITEK Compact. Antimicrobial susceptibility tests, phenotypic ESBL and E-tests were performed conventionally. Real-time PCR was utilized to detect presence of O25b-ST131 clone, blaCTX-M-15 and blaCTX-M-1. Results: O25b-ST131 clone, CTX-M-1 and CTX-M-15 were detected in 22%, 73%, 37% in UTIs, respectively. Presence of O25b-ST131 clones and CTX-M-1 genes among E. coli strains isolated from inpatients were found statistically higher than outpatients. The most effective choice was found to be fosfomycin and nitrofurantoin in outpatients and inpatients, respectively. The MIC90 values of Amikacin, Cefotaxime, Cefepime and Ciprofloxacin were higher in inpatients than in oupatients, whereas Cefotaxime and Ciprofloxacin MIC50 values were found to be higher in inpatients than in outpatients. The highest increase of MIC90 values was observed in O25b-ST131, CTX-M-1 and CTX-M-15 coexistence. Conclusion: The presence of O25b-ST131 clone, CTX-M-1 and CTX-M-15 genes in E. coli strains in patients with UTI has been revealed. In the presence of the O25b-ST131 clone, a significant increase was observed in the ciprofloxacin MIC values indicating the importance of monitorization of the clone using molecular epidemiology. Keywords: O25b-ST131, Escherichia coli, UTI, CTX-M-15, Real-time PCR